2017
DOI: 10.1080/21645515.2017.1394533
|View full text |Cite
|
Sign up to set email alerts
|

Addressing barriers to vaccine acceptance: an overview

Abstract: Addressing the drivers of vaccine hesitancy and the barriers to vaccine acceptance is a complex but important task. While the percentage of hesitant does vary from country to country and in time few, if any, countries are ever free from this problem. Overcoming hesitancy requires detection, diagnosis and tailored intervention as there is no simple strategy that can address all of the barriers to vaccine acceptance. Immunization program managers and health care workers need to become adept at recognizing and ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
90
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 64 publications
(84 reference statements)
1
90
0
4
Order By: Relevance
“…Unvaccinated children in the 2017 NIS-Child were disproportionately uninsured: 17.2% of unvaccinated children were uninsured, compared with 2.8% of all children. Evidence-informed strategies addressing parents’ decisions about vaccinating their children could focus on both programs and individual patients, such as vaccine delivery through school programs, strong recommendations by providers to parents to vaccinate their children, and reinforcement of the importance of community protection through vaccination ( 7 ). …”
Section: Discussionmentioning
confidence: 99%
“…Unvaccinated children in the 2017 NIS-Child were disproportionately uninsured: 17.2% of unvaccinated children were uninsured, compared with 2.8% of all children. Evidence-informed strategies addressing parents’ decisions about vaccinating their children could focus on both programs and individual patients, such as vaccine delivery through school programs, strong recommendations by providers to parents to vaccinate their children, and reinforcement of the importance of community protection through vaccination ( 7 ). …”
Section: Discussionmentioning
confidence: 99%
“…To maximize uptake, educational and vaccination campaigns should align with communities’ preferences for delivery on weekend, door-to-door and by volunteers from the same communities. Educational and engagement efforts should target key influencers such as elders and religious leaders and also be embedded in services for key groups such as pregnant women [32] , [33] . Based on our research, education should provide information on vaccines’ aim and possible adverse effects, to limit the spread of rumours and distrust.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our research, education should provide information on vaccines’ aim and possible adverse effects, to limit the spread of rumours and distrust. Furthermore, to address misconceptions about vaccine effectiveness and prevent future frustration leading to vaccine hesitancy, vaccine-related education should be pre-emptive, differentiate between vaccines and other medical products using clear language, and be clear with regards to the effectiveness of different vaccines [33] . Increased transparency and information to communities through trained community advisory boards selected from the same community also seems a promising approach to improve understanding [34] .…”
Section: Discussionmentioning
confidence: 99%
“…Many healthcare professionals still maintain skepticism about maternal vaccinations, which can be easily transferred to the patients. 31 A consistent message across an entire healthcare workforce will fill in maternal knowledge gaps which will in turn reduce vaccine hesitancy. Secondly, SAGE, which already notes knowledge, attitudes, and beliefs as drivers of vaccine hesitancy, should prioritize acceptability in their review for a new vaccine introduction for maternal vaccines, as research outlined above has indicated its importance in maternal decision-making and ultimate vaccine uptake.…”
Section: Moving Forwardmentioning
confidence: 99%
“…27 A strong communication strategy should also include culturally and contextually appropriate messaging that addresses the values, beliefs and norms of the groups and subgroups of populations, to address the attitudes and beliefs that could influence a mother's intention to vaccinate. 31 Maternal vaccines contain great potential to reduce the global burden of infant morbidity and mortality, with their unique position to access the infant's immune system through maternal antibodies before a child vaccine could be effective. However, vaccine hesitancy, driven largely by maternal knowledge of vaccines, threatens to curtail the potential successes of such vaccines, thereby hindering public health goals to reduce the global burden of neonatal infectious disease and mortality.…”
Section: Moving Forwardmentioning
confidence: 99%